Coalescence mechanism of helium bubble during tensile deformation revealed by in situ small-angle X-ray scattering. (1st January 2019) - Gao, Jie; Huang, Hefei; Liu, Jizhao; Zeng, Jianrong; Xie, Ruobing; Li, Yan
Abstract: Helium nanobubbles created in nickel foil under helium ion irradiation are studied using the combination of small-angle X-ray scattering (SAXS) measurement and transmission electron microscopy (TEM) characterization. The log-normal distribution of bubble sizes obtained by SAXS agrees rather well with the TEM results. Under the tensile stress, SAXS experiments were carried out to follow in situ the evolution of helium nanobubbles. A detailed analysis revealed that the bubbles performed coalescence via the elongation in the direction of tensile stress loading. Our finding demonstrated that bubble "deformation and coalescence" mechanism was also applicable in bubble growth under external stress. Graphical abstract: The "Deformation and Coalescence" coarsening mechanism of helium bubbles during tensile deformation revealed by in situ small-angle X-ray scattering. Unlabelled Image